ANALISIS KUALITAS LAYANAN MOBILE BANKING TERHADAP KEPUASAN PELANGGAN (Studi Pada Bank X Area Semarang) - Purnomo, Andreana Yulia; Dwiyanto, Bambang Munas (Faculty of Economics and Business Diponegoro University, 2017)
All activities nowadays are based on technology include in banking industry. One of the innovations that made banks which associated with the development of technology is the use of mobile banking. The aim of this study is to analyze whether electronic service influence on customer satisfaction.The sample in this study were 160 respondents that had used mobile banking, with non-probability samples with analytical method used is multiple linier regression using SPSS 23.The results of this study showed that the five independent variables has a positive and significant to the dependent variables, realiability(0,217), responsiveness (0,264), Assurance (0,200), Empathy (0,204) and Tangibles (0,120) to customers satisfaction